2016
DOI: 10.1111/jai.13198
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic trials with mirrors do not elicit the same aggressiveness of a real trial in the matrinxã fish,Brycon amazonicus(Spix & Agassiz, 1829)

Abstract: This study tested the efficacy of mirror trials in studying aggressiveness in the matrinxã fish, Brycon amazonicus. The hypothesis was that a mirror would elicit an aggressive response in B. amazonicus juveniles, but show different behavioral and physiological profiles than those observed in trials with real opponents. Fish were tested using either a mirror trial (n = 7) or a real trial (n = 7), that is, placed alone with a mirror or paired with a same-sized opponent, respectively. All trials lasted for 20 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…This result was contradictory to our hypothesis, which was based on several studies showing an inhibition of aggression after FLX treatment (Perreault et al 2003;Lynn et al 2007;Kania et al 2012;Forsatkar et al 2013). Furthermore, cortisol levels after 20 min of fighting with a same-sized conspecific intruder were consistent with the literature (Wolkers et al 2014;Serra et al 2016), with no significant difference between the treatments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result was contradictory to our hypothesis, which was based on several studies showing an inhibition of aggression after FLX treatment (Perreault et al 2003;Lynn et al 2007;Kania et al 2012;Forsatkar et al 2013). Furthermore, cortisol levels after 20 min of fighting with a same-sized conspecific intruder were consistent with the literature (Wolkers et al 2014;Serra et al 2016), with no significant difference between the treatments.…”
Section: Discussionsupporting
confidence: 89%
“…Fighting is stressful for fish (Øverli et al 1999, 2004), and even after 12 h of FLX treatment, matrinxãs were able to properly respond to this stressor, reaching cortisol levels that were similar to the control group and consistent with cortisol levels observed in matrinxã (control fish) after a similar fight paradigm demonstrated in previous studies (Wolkers et al 2014;Serra et al 2016). In jundiá Rhamdia quelen juveniles, a short (17 min) exposure to FLX in the water also altered the behavior (had an anxiolytic effect) without impairing the stress response (Abreu et al 2016).…”
Section: Discussionsupporting
confidence: 82%
“…In such cases, mirror presentations might miss crucial parts of the communication occurring during aggressive encounters. Accordingly, several studies showed diverging aggressive responses of fishes tested against mirror images or live opponents (Arnott et al, 2016;Balzarini et al, 2014;Elwood et al, 2014;Li, et al, 2018a;Li, et al, 2018b;Ruzzante, 1992;Serra et al, 2017;Verbeek et al, 2007). Furthermore, even if aggressive behaviours towards a mirror image and a live opponent are comparable, differences in hormonal response or brain activity indicate that contestants discriminate between a conspecific and a mirror image.…”
Section: Introductionmentioning
confidence: 99%